The effects of dietary energy level on the growth performance of yaks (Bos grunniens) were studied based on omics technique - Jiang, Yahui; Zhang, Jiali; Wang, Kaiwen; Feng, Hengbo; You, Yuting; Dai, Peng; Wang, Zhisheng; Hu, Rui; Peng, Quanhui; Zou, Huawei; Xiao, Jianxin; Wang, Lizhi; et al. (Frontiers in Microbiology, 2025)
IntroductionThe yak (Bos grunniens) is uniquely adapted to the Qinghai–Tibet Plateau, yet nutritional guidelines for yaks remain limited and often follow cattle standards. This study aimed to clarify dietary energy requirements to improve yak feeding strategies.MethodsFattening yaks were assigned to three diets with different net energy for gain (NEg): low (LE, 4.06 MJ/kg), medium (ME, 4.46 MJ/kg), and high (HE, 4.87 MJ/kg), with 13% crude protein constant. Growth performance, apparent digestibility, serum biochemistry, hormones, and rumen fermentation were measured. Additional, 16S rDNA sequencing analyzed the rumen and fecal microbiota, and serum non-targeted metabolomics profiling was performed.ResultsResults showed that ME and HE diets significantly increased average daily gain and nutrient digestibility while reducing feed conversion ratios (P < 0.05). Serum glucose, triglycerides, and growth-related hormones were higher in ME and HE groups, while non-esterified fatty acids was significantly decreased (P < 0.05). Higher energy diets increased microbial protein and reduced ruminal ammonia nitrogen. The ME diet increased ruminal Proteobacteria, enhancing fermentation and soluble carbohydrate utilization, while promoting fiber-degrading UCG-005. High energy diets elevated fecal Spirochaetota and Treponema abundances. Metabolomics revealed differences mainly in lipidrelated metabolites correlated with specific microbial taxa.DiscussionIn conclusion, increasing dietary energy improves growth, nutrient utilization, and beneficial microbiota profiles in yaks. A medium-energy diet (NEg: 4.46 MJ/kg) optimizes fermentation and microbial balance, providing a scientific basis for precise nutritional strategies in yak production on the Qinghai–Tibet Plateau.